2011
DOI: 10.1111/j.1399-3046.2011.01608.x
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral replacement with appendix in pediatric renal transplantation

Abstract: Ureteral necrosis is an uncommon complication following RT which can adversely affect outcome. Even though authors agree that the native ureter ought to be preserved, there are cases in which graft function can only be salvaged by ureteral substitution. The scant references in the literature on the use of the appendix for left ureteral replacement in children prompted us to report the following two cases in whom the technique was employed and to assess the evolution of graft function in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…Postoperative complications such as thrombosis, severe urinary tract infection and ureteral necrosis may occur and improper use often requires nephrectomy. 22 In conclusion, intermittent hydronephrosis associated with abdominal pain occurred in older children, and IVP or magnetic resonance imaging indicated a filling defect in the ureter, highly suggestive of polyp induced hydronephrosis. How to understand the length of polypoid ureteral lesions before surgery still needs to find a better examination method to facilitate the formulation of preoperative surgical plan.…”
Section: Discussionmentioning
confidence: 75%
“…Postoperative complications such as thrombosis, severe urinary tract infection and ureteral necrosis may occur and improper use often requires nephrectomy. 22 In conclusion, intermittent hydronephrosis associated with abdominal pain occurred in older children, and IVP or magnetic resonance imaging indicated a filling defect in the ureter, highly suggestive of polyp induced hydronephrosis. How to understand the length of polypoid ureteral lesions before surgery still needs to find a better examination method to facilitate the formulation of preoperative surgical plan.…”
Section: Discussionmentioning
confidence: 75%
“…There are a limited number of studies in the literature that performed appendiceal interposition to left ureteral defects [5] , [6] , [9] , [10] , [11] . In the literature review, it was observed that appendix interposition was applied to the left ureter in 15 of 64 patients [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] . Complications have been reported to be higher in appendiceal interposition surgeries using isoperistaltic [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Double J catheters are used in the treatment of conditions such as ureteral reconstructive surgery, obstructive uropathy, extracorporeal real shock wave lithotripsy, and obstructive anuria [14] . Ureteral stents are also used during intestinal interpositions applied to ureteral defects [5] , [6] , [7] , [8] , [11] , [12] . Forgetting and not removing these catheters cause high complications [14] .…”
Section: Discussionmentioning
confidence: 99%
“…previous option as is evident from this study. 3,5 Appendix although appears a gold standard and ideal for right sided replacements owing to its adequate narrow lumen for substitution in children and its good mesentry and pedicled blood supply there are limitations to it. 6 Sometimes inadequate length of appendix and its pedicle or its twisting or drag on trying to use it on left side can limit its usage.…”
Section: Discussionmentioning
confidence: 99%